Negotiating sovereignty and human right [ actors and issues in contemporary human rights politics - Cox, Michaelene; Shawki, Noha (Ashgate, 2009)
Presenting an overview of institutional developments and innovations in human rights politics, this book discusses some of the most important human rights issues. It focuses on actors and/or issues that are outside the mainstream of international human rights politics